Effects of the Inclusion of Star Gooseberry (Sauropus androgynus) Leaf Meal in Ration on Physical and Nutritional Quality of KUB Chicken Breast Meat - Anggraeni Anggraeni; Burhanudin Malik; Dewi Wahyuni; Novi Sidroh Farida; Wira Fadillah Suroso (Faculty of Animal Science, Universitas Brawijaya, 2022)
Local chickens are among the enormous poultry genetic sources in Indonesia. These chickens are potential to develop as they are found in big population throughout the country. Chicken meat is a nutritious food containing nutrients including carbohydrate, protein, fat, water, minerals, and vitamins in balanced proportion. Improvement of nutritive contents of Balitnak Superior Local Chicken (KUB chicken) meat can be achieved by providing the chickens with quality and nutritious feed. The inclusion of star gooseberry leaf meal can be an alternative as it is nutritious, cheap, and plenty. This study was aimed at assessing effects of star gooseberry leaf meal (SGLM) inclusion in ration on physical and nutritional quality of KUB chicken breast meat. Ninety-six (KUB chickens) aged 7 days were allocated into 4 treatments and 4 replicates in a completely randomized design. Treatments consisted of 0% SGLM inclusion in ration (R0), 1% SGLM inclusion in ration (R1), 2% SGLM inclusion in ration (R2), and 3% SGLM inclusion in ration (R3). Data were subjected to an analysis of variance (anova) and a Duncan test. Results showed that treatments significantly increased (P<0.05) water but not (P>0.05) ash, fat, and protein contents of breast meat. Meat water holding capacity, cooking loss, and tenderness were found to be improved (P<0,05) but no different (P>0.05) meat pH was observed.